AGENDA PENEGAKAN HUKUM DAN RELEVANSINYA BAGI PEMBANGUNAN BANGSA - Gunarto Gunarto (Jurnal Pembaharuan Hukum, 2014)
There are some very influential on the fact that the law enforcement paradigm. First, the tendency of the system broadest autonomy so that it can be federalism. Second, the tendency of a multiparty system that affect the presidential cabinet system that had been adopted in 1945. Third, the tendency of separation (not distinction) expressly (separation not differentiation) between the executive, legislative, and judicial branches. greatly affect the law making process (LMP), and law enforcement process (LEP). Fourth, the inclusion of the effects Governmental Organization (NGO) in the government decision-making and legislative process is sometimes influential in the process of justice. Fifth, the presence of MPR RI who ordered the President to carry out the government’s eradication of corruption and creating a clean and respectable further increase the burden of government is not smaller in the present and the future. Therefore, the development of national law reform period is now a transition from the previous system to a democratic system of government that promote transparency, accountability, and human rights, and than can open public access to government performance.